Objective Clinical and Radiological Response under Sunitinib in a Case of Thigh Hidradenocarcinoma - S. Korbi; H. Rachdi; H. El Benna; N. Mejri; Y. Berrazaga; N. Daoud; S. Labidi; H. Boussen (Case Reports in Oncological Medicine)
A 56-year-old male was treated by local surgery in 1968 and 2005 for a left thigh lesion. A 2nd local relapse occurred in 2015 and was treated by complete macroscopic surgery with histology concluding to a hidradenocarcinoma. A 3rd locoregional relapse occurred in October 2018, with the presence of inflammatory ulcerated lesions. A 2nd histology and immunohistochemistry exam showed a proliferation positive for CK, CK5, and p63 suggesting the diagnosis of hidradenocarcinoma. The patient was treated by 3 lines of chemotherapy, 1st by Adriamycin, 2nd by carboplatin-paclitaxel, and then 3rd by oral capecitabine, leading to a stable clinical disease but without a clinical benefit. A locoregional plus metastatic lung progression was observed in March 2019, with the presence of lung nodules and retroperitoneal lymph nodes, multiple skin left thigh and left inguinal ulcerated lesions. The patient received then in 4th line in April 2019 oral sunitinib at 50 mg daily, with 4 weeks therapy/2 weeks pause. Side effects were represented by mucositis, anorexia, weight loss, and fatigue. We observed since the 1st week of therapy a fast response, with a decrease of the ulcerated lesions, a skin loss, and deep hemorrhagic areas. CT-scan showed after 2 weeks of sunitinib an objective response on both locoregional and metastatic lesions.